profile-img
Aparna Dash Asked a Question
December 30, 2020 3:18 pmpts 30 pts
51. logb a log. a - log, a og a log a log b loggc Let log a= A, log b = B and log c = C log a (log b) (log c) -1- Then, log, a loge a-log, a = A2 -1 BC B2 Similarly, loga b log. b- logp b= 1 CA and loga C log, C -loge C = - -1 AB (log, a log, a- loga a) + (logą b loge b - log, b) +(l09, C log, C - log. C) = 0 2 A-1+5-1+ C 1 0 A2 BC CA AB or A3 +B +C3 3ABC = 0 A+B+C = 0 log a +log b + log c =0 log (abc) =0 abc
  • 1 Answer(s)
  • 0 Likes
  • 2 Comments
  • Shares
  • Deepak singh thankyou
    Refer attached step marked is derived from this formula .
    • cropped2416916111348395739.jpg
    Likes(0) Reply(0)
  • Aparna Dash
    here is the question.
    • cropped7597421357437090391.jpg
    Likes(0) Reply(0)
Head Office :
MPA 44, 2nd floor, Rangbari Main Road,
Mahaveer Nagar II, Kota (Raj.) – 324005

Corporate Office:
212, F-1, 2nd Floor, Evershine Tower,
Amrapali Marg,
Vaishali Nagar, Jaipur (Raj.) – 302021

Mail: info@eduncle.com
All Rights Reserved © Eduncle.com